Sociology AS for AQA - Moore, Stephen, 1950-; Aiken, Dave, 1955-; Chapman, Steve, 1957- (London : Collins, 2008)
This is an accessible textbook designed to meet the specific requirements of AS Level sociology students, written by practising teachers and examiners.
Previous edition: 2005.
Includes bibliographical references and index.
Keywords: Sociology; Sociology -- Problems, exercises, etc; Society